KARAKTERISTIK SENSORI DAN FISIKOKIMIA PERMEN JELLY UBI CILEMBU (IPOMOEA BATATAS (L). LAM) CV. CILEMBU DENGAN GELLING AGENT KARAGENAN DAN GELATIN - hutami, Rosy; Handayani, Ani; Rohmayanti, Titi (Universitas Djuanda, 2019)
This study aimed to determine the effect of the concentration of sweet potato juice to the sensory, physical, and chemical characteristics of Cilembu sweet potato jelly candy. This study was divided into two stages, including the determination of the concentration of sweet potato juice and determination of the amount of gelling agent. Each treatment using a separate experimental design namely, completely randomized design (CRD). The selected concentration of sweet potato juice in the Stage I was 55%. The level of carrageenan and gelatin significantly affected to the color, taste, elasticity, hardness, and adhesiveness. The selected treatment of sweet potato jelly candy with carrageenan has a 34.78% water content, 1.25% ash content, 32.41% reducing sugar, 36.64% sucrose, and Aw 0.87. The selected treatment of sweet potato jelly candy with gelatin has a 22.62% water content, 0.56% ash content, 34.65% reducing sugar content, 35.77% sucrose, and Aw 0.82. Based on the results of the Independent Sample T-test, sweet potato jelly candy with gelatin has a more chewy texture and sweeter than the carrageenan one. It also has a better preference value on the aroma, texture, and taste parameter and also has lower water content and Aw.